2018
DOI: 10.13031/trans.12481
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Ammonia and PM Generation of Cage-Free Henhouse Litter with Solid Additive and Liquid Spray

Abstract: A number of chain restaurants, retailers, and grocers in the U.S. have pledged to source only cage-free (CF) eggs in the foreseeable future (e.g., by 2025) due to marketing reasons or concerns over animal welfare. However, CF housing has some inherent challenges, and a predominant one is poor air quality, i.e., ammonia gas (NH3) and particulate matter (PM), and increased emissions. Spraying a liquid agent such as electrolyzed water (EW) can effectively suppress PM generation of CF henhouse litter. However, liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 24 publications
(27 reference statements)
1
19
0
Order By: Relevance
“…At the same time, welfare standards of hens continue to elevate, and some of the criteria (e.g., allocation of enrichment, housing systems, and management practices) are subject to debate [1][2][3][4] . Transitioning of egg production systems from conventional cage to alternative housing (e.g., enriched colony, aviary cage-free) is increasingly occurring in various parts of the world, especially in Europe and the United States, to meet animal welfare requirements or legislation [5,6] .…”
Section: Introduction mentioning
confidence: 99%
“…At the same time, welfare standards of hens continue to elevate, and some of the criteria (e.g., allocation of enrichment, housing systems, and management practices) are subject to debate [1][2][3][4] . Transitioning of egg production systems from conventional cage to alternative housing (e.g., enriched colony, aviary cage-free) is increasingly occurring in various parts of the world, especially in Europe and the United States, to meet animal welfare requirements or legislation [5,6] .…”
Section: Introduction mentioning
confidence: 99%
“…1a) so that other types of liquid agents (e.g., electrolyzed water or slightly acidic electrolyzed water) may be sprayed as well in the future. During the lab study that preceded the field verification test, a spray dosage of 125 mL m -2 corresponding to 1 cm litter depth had been shown to achieve over 50% PM reduction without causing NH3 problem (Chai et al, 2017(Chai et al, , 2018a. This spray dosage was used as the base and adjusted according to the litter depth (table 1).…”
Section: Laying-hen House and Sprinkling Systemmentioning
confidence: 99%
“…Application of low pH liquid to the litter would help control PM and ammonia at the same time, but concerns arise about the potential corrosive effect of acidic liquid on the housing equipment. Chai et al (2018a) conducted research in dynamic emission chambers by spraying neutral electrolyzed water (pH=7-8) at 125 mL m -2 (corresponding to litter depth of 1 cm) and applying PLT TM litter additive at 30 g per kg dry litter onto CF henhouse-collected litter, which reduced the generation of PM by 60-70% and NH3 by 70-80%, respectively. Properly controlling the water spray dosage could maintain over 50% PM reduction efficiency without causing NH3 issue.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported reduction of 60-70% in PM generation and 70-80% in NH3 generation. Chai et al (2018a) also showed that properly controlling water spray dosage could provide >60% PM reduction efficiency without causing an increase in NH3 concentrations.…”
Section: Introductionmentioning
confidence: 97%
“…However, concerns exist about the potential corrosive effect of acidic liquid on housing equipment (Chai et al, 2017). Chai et al (2018a) conducted a lab-scale study that involved spraying neutral electrolyzed water (pH=7-8) at 125 mL m -2 (at 1 cm litter depth) and applying poultry litter additive/treatment (PLT, sodium bisulfate, NaHSO4) at 30 g per kg dry litter onto CF henhouse litter. The authors reported reduction of 60-70% in PM generation and 70-80% in NH3 generation.…”
Section: Introductionmentioning
confidence: 99%